Revision der durch Franz Lengersdorf bearbeiteten Sciaridae (Diptera, Nematocera) von Taiwan. - Menzel, Frank; Mohrig, Werner (Contributions to Entomology = Beiträge zur Entomologie, 1991)
In the collection of the Institut für Pflanzenschutzforschung Kleinmachnow, Bereich Eberswalde, Abt. Taxonomie der Insekten there are 20 males and 79 females of Sciaridae, collected by H. Sauter in Taiwan. There is described a new method for the preparation of dry mounted specimens on slides. All males and one female of the Taiwan collection were mounted on slides. Three species were new combined: Lycoriella pammela (Edwards, 1928), Peniosciara cornuta (Lengersdorf, 1927) and Bradysia dissimilis (Lengersdorf, 1927). Redescription of Sciara copiosa Lengersdorf, 1927, Eurysciara cornuta (Lengersdorf, 1927), Bradysia dissimilis (Lengersdorf, 1927) and Peniosciara cornuta (Lengersdorf, 1927) are given, Bradysia sauteri is described as new. All taxonomic and faunistic data given by Lengersdorf (1927) were checked, corrections to these data are given. Nomenclatural Acts dissimilis (Lengersdorf, 1927) (Bradysia), comb. n. hitherto Sciara dissimilis sauteri Menzel & Mohrig, 1991 (Bradysia), spec. n. pammela (Edwards, 1928) (Lycoriella), comb. n. hitherto Sciara pammela cornuta (Lengersdorf, 1927) (Peniosciara), Lectotype; comb. n. hitherto Plastosciara cornuta